THE VALUE OF GEORGE ELIOT’S WORKS FOR LITERATURE AND BRITISH CULTURE - Akhmedova, Gavkharoy (Educational Research in Universal Sciences, 2023)
George Eliot was certainly one of the most influential women of her Era. George Eliot was known for her genius at writing intelligent novels that address societal and historical issues. Eliot began her career with all sorts of obstacles in her way: she was not rich; she was not pretty; she had no pedigree or social standing. But she wrote and developed as a writer even at a time when women were discouraged from intellectual work. This paper will demonstrate the importance of George Eliot’s works for literature.